Pemulihan Moral dan Spiritual: Peran Pastoral dalam Mendukung Pasangan Terlibat dalam Perselingkuhan - j, jojonikus; Wahyuni, Sri (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2024)
This study aims to examine the role of pastoral care in supporting couples involved in infidelity to achieve moral and spiritual recovery. Through a qualitative approach, the research explores various strategies and approaches that can be employed by pastors and church ministers to help couples navigate the crisis in their relationship caused by infidelity. The findings indicate that infidelity has a significant impact on the emotional and psychological well-being of the couples, requiring sensitive and holistic handling during the recovery process. The conclusion of this study emphasizes the importance of welltrained and empathetic pastoral care in assisting couples to restore their relationships. The study recommends enhanced training for church ministers in addressing infidelity cases and the development of comprehensive and sustainable recovery programs.